Diphtheria: A Disease of the Past or a Public Health Threat? Prevention Strategies in the 21st Century - Pabis, Gabriela; Strzelczyk, Magdalena; Koziołek, Iwona; Bętkowska, Paula; Wziątek, Joanna; Kowalik, Piotr; Fatyga, Patrycja; Fatyga, Wiktoria; Krzyżanowska, Daria; Dowierciał, Kinga (Quality in Sport, 2025)
Introduction and purpose: Diphtheria is an infectious, potentially fatal disease caused by the aerobic, Gram-positive bacillus Corynebacterium diphtheriae. For many years, it posed a significant health threat, particularly among children. The introduction of mass immunization programs led to a substantial decline in the number of cases, and in some countries, the disease was nearly eradicated. However, in recent years, a resurgence of diphtheria has been observed, which is linked to factors such as declining vaccination rates and increased human migration. The aim of this paper is to review the current knowledge on diphtheria, its epidemiological status, and strategies for its prevention. Material and Methods: Bibliographic research was limited to papers published between 2019 and 2025. The articles were identified using the PubMed and Google Scholar search, using key terms. Key terms: diphtheria, Cornyebacterium diphtheriae, vaccination coverage, disease reemergence, vaccination hesitancy Results: A review of the literature and epidemiological data indicates that, although diphtheria was once nearly eradicated, it continues to re-emerge in the population. This resurgence is primarily attributed to declining vaccination coverage and increased population migration. Such a trend poses serious consequences at both the individual and societal levels. Prevention strategies to curb the spread of diphtheria include maintaining high vaccination coverage, promoting health education particularly regarding immunization and combating misinformation spread through social media. Conclusions Problem highlights the urgent need for preventive strategies focused on increasing vaccination coverage, combating misinformation on social media, and improving access to immunization services. Only integrated and coordinated efforts can ensure that the disease remains under control.